Changes in Herbaceous Species Composition in the Absence of Disturbance in a Cenchrus biflorus Roxb. Invaded Area in Central Kalahari Game Reserve, Botswana. (12th June 2011) - Makhabu, Shimane W.; Marotsi, Balisana
Abstract : A-nine year study was carried out to investigate changes in herbaceous species composition in an area invaded by Cenchrus biflorus Roxb, an exotic invader grass species. The study ensued termination of livestock and human activities in the area when residents of the area were relocated to another area. Vegetation characteristics from the disturbed sites (previous occupied areas) and undisturbed sites (previously unoccupied areas) were determined. The results show that C. biflorus has high tolerance to disturbance. It comprised the larger proportion of grasses in disturbed sites at the inception of the study. However, it decreased in abundance with time in disturbed areas and was absent in the undisturbed areas, suggesting that its ability to invade undisturbed sites is limited. Perennial species successfully reestablished on the third year after termination of disturbance. The study reveals that C. biflorus invasion in the Kalahari ecosystem can be controlled by termination of disturbances.